Influence of shaped charge jet state on its interaction with ERA flying plate - Nicolas Reboul; Ashwin Chinnayya; Frédéric Paintendre; Simon Dalle Piagge; Vincent Jaulin; Jérôme Limido; Anthony Collé; Fabien Rondot (Defence Technology, 2025)
The Explosive Reactive Armors (ERA) are really efficient at reducing Shaped Charge Jet (SCJ) performance. The main destabilizing mechanism is the transverse movement of the front and rear moving plates (MP) on the SCJ. Therefore, a good understanding of the interaction SCJ/MP is essential for improving both weapon and armor systems. In a previous article, we have shown that interaction regimes are mainly influenced by the local collision geometry. Thus, in the collision point frame, the angle of collision between the continuous SCJ and the MP is a key parameter. This flow angle is acute for the Backward Moving plate (BMP) moving against the SCJ and obtuse for the Forward Moving Plate (FMP) moving alongside it. In the former, the jet is simply deflected, which is the regime 1 of deflection. In the latter, the interaction turns on an alternative creation of fragment and ligament, which is the regime 2. Fragments are parts of the jet that are only slightly deflected while ligaments are the curved material bridges that connect two consecutive fragments.When stretching, the jet is systematically subject to instabilities that disturb its surface, creating necks along it. Their growth finally leads to the jet fragmentation. In this article, we focus on this jet disturbance and its consequences on the SCJ/MP interaction.An experimental set-up was built to implement the interaction between a SCJ and a moving plate for different collision points, at different stand-off distances. The plate can interact with a smooth SCJ or a disturbed SCJ at a close and a far stand-off distance, respectively.One of the main results is the visualization of a regime change in SCJ/BMP interaction. A regime 1 (deflection) interaction changes into a ligament regime interaction (similar to a FMP regime 2) when the collision point stand-off is increased. It is proposed that this change can be attributed as the increase of the amplitude of the jet surface disturbances. This phenomenon is well captured by the γSPH simulations. Finally, using both experimental and numerical approaches, we propose a new detailed analysis of the different phenomena occurring during the interaction between a disturbed-surface jet and a moving plate. Interaction regime changes are linked to jet local geometry changes. The interactions of a BMP with a smooth SCJ or with a disturbed surface SCJ are geometrically not the same and, thus, generate different local flows and interaction mechanisms.However, some other simulations have been carried out with constant velocity jet whose surface has been previously disturbed. These simulations underline the influence of both disturbance wavelength λ and amplitude A on the interaction regimes.Surface disturbances of the SCJ, linked to its stretching, have a major influence on its interaction with a moving plate.